The accuracy of prenatal diagnosis of major congenital heart disease is increasing. (2nd April 2020) - Lytzen, Rebekka; Vejlstrup, Niels; Bjerre, Jesper; Bjørn Petersen, Olav; Leenskjold, Stine; Keith Dodd, James; Stener Jørgensen, Finn; Søndergaard, Lars
Abstract: Regular audit of results of prenatal screening for congenital heart disease (CHD) is crucial to ensure reliable prenatal diagnosis. We aimed to assess the accuracy of prenatal diagnosis of major CHD between 1996 and 2013. During the study period, prenatal detection of major CHD improved from 4.5% to 71.0% ( p <.001). Prenatal diagnoses on 628 live born children and terminated pregnancies were compared with postnatal findings or autopsy reports. The proportion of correct diagnoses increased throughout the study period from 42.9% in 1996 and reached 88.2% in 2013 ( p <.001). A total of 32 foetuses with suspected major CHD were terminated though no major CHD was found at autopsy. In these pregnancies, termination was mainly performed due to other anomalies in the foetus. Along with improved detection of major CHD, the validity of a prenatal diagnosis is increasing. No cases of misinterpreted major CHD resulted in the termination of a healthy foetus in this study. Impact statement: What is already known on this subject ? Prenatal diagnosis of isolated congenital heart disease (CHD) correlates well with lesions found during autopsy performed in terminated foetuses. Few studies have assessed the accuracy of prenatal diagnosis of major CHD in live born children, cases with associated anomalies and the time trend in validity. What the results of this study add ? This study illustrates that the validity of prenatal diagnosis of major CHD is increasing. Prenatal diagnoses in terminated pregnancies as well as in live born children is high except for coarctation of the aorta and atrioventricular septal defects. Chromosomal anomalies are associated with lower accuracy of prenatal diagnosis. What the implications are of these findings for clinical practice and/or further research ? Prenatal diagnosis is an accurate tool for detecting major CHD. Misinterpretation has not led to the termination of a healthy foetus; however, this study illustrates that vigilant care should be placed on the cardiac evaluation when termination is considered due to the cardiac defect.